3(5x-7)-2(9x-11)=4(8x-13)-17
Answers
Answered by
17
Here is your answer ⤵⤵⤵⤵⤵⤵⤵
3(5x-7) -2(9x-11) = 4(8x-13) -17
=> 15x-21-18x+22 = 32x-52-17
=> 15x-18x-21+22 = 32x-52-17
=> -3x+1 = 32x-69
=> -3x-32x = -69-1
=> -35x = -70
=> -x = -70/35
=> -x = -2
=> x = 2
HOPE IT HELPS YOU ☺☺ !!!
3(5x-7) -2(9x-11) = 4(8x-13) -17
=> 15x-21-18x+22 = 32x-52-17
=> 15x-18x-21+22 = 32x-52-17
=> -3x+1 = 32x-69
=> -3x-32x = -69-1
=> -35x = -70
=> -x = -70/35
=> -x = -2
=> x = 2
HOPE IT HELPS YOU ☺☺ !!!
saurabhsinghbihari:
hii
Answered by
10
Heya...
![3(5x - 7) - 2(9x - 11) = 4(8x - 13) - 17 \\ 15x - 21 - 18x + 22 = 32x - 52 - 17 \\ - 3x + 1 = 32x - 69 \\ - 3x - 32x = - 69 - 1 \\ - 35x = - 70 \\ x = \frac{70}{35} = 2 3(5x - 7) - 2(9x - 11) = 4(8x - 13) - 17 \\ 15x - 21 - 18x + 22 = 32x - 52 - 17 \\ - 3x + 1 = 32x - 69 \\ - 3x - 32x = - 69 - 1 \\ - 35x = - 70 \\ x = \frac{70}{35} = 2](https://tex.z-dn.net/?f=3%285x+-+7%29+-+2%289x+-+11%29+%3D+4%288x+-+13%29+-+17+%5C%5C+15x+-+21+-+18x+%2B+22+%3D+32x+-+52+-+17+%5C%5C+-+3x+%2B+1+%3D+32x+-+69+%5C%5C+-+3x+-+32x+%3D+-+69+-+1+%5C%5C+-+35x+%3D+-+70+%5C%5C+x+%3D+%5Cfrac%7B70%7D%7B35%7D+%3D+2+)
Hope it helps..!!
Hope it helps..!!
Similar questions